In Children and Adolescents (Ages 6-17) With Attention Deficit Hyperactivity Disorder (ADHD), How Does Viloxazine Extended-Release (ER) Compare with Placebo or Other ADHD Medications in Terms of Improving ADHD Symptoms, Adverse Events and Treatment Discontinuation Rates? A Systematic Review - Khushboo Kansal; Betsy Marina Babu; Gaurav Uppal; Nadia Liaqat; Asha Dhandapani (BJPsych Open)
Aims: In this systematic review, the effectiveness and safety of viloxazine ER in the treatment of ADHD in children and adolescents aged between 6–17 years will be assessed.